Pengaruh Penyuluhan terhadap Tingkat Pengetahuan dalam Pencegahan HIV/AIDS pada Remaja di SMAN-1 Palangka Raya - Panueh, Jovanka Mangium Wijayanti; Martani, Natalia Sri; Toemon, Angeline Novia (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Human Immunodeficiency Virus (HIV) is a virus that infects cells of immune system, destroys or impairs their function so it can cause progressive damage of the immune system which leads to Acquired Immunodeficiency Syndrome (AIDS). Adolescent knowledge about reproductive health is generally influenced by education, personal experience, culture and mass media. The provision of adequate and factual information about HIV/AIDS allows a teenager to raise awareness, an understanding and behave according to the knowledge they has. The purpose of this study is to determine the effect of counseling on the level of knowledge in preventing HIV/AIDS among students at SMAN-1 Palangka Raya. This study used a Quasy-experimental design, a one group pretest posttest design, with a simple random sampling technique. The data analysis used is the Wilcoxon test. The results showed that the level of knowledge of adolescents about HIV/AIDS at SMAN-1 Palangka Raya before being given counseling was mostly in the less category as many as 57 people (57%), then the level of knowledge of teenagers about HIV/AIDS after being given counseling was mostly in the good category as many as 91 people (91%). There is an influence in the provision of counseling on the level of knowledge of adolescents about HIV/AIDS at SMAN-1 Palangka Raya.